Effects of climate variability on an estuarine green crab Carcinus maenas population. (July 2021) - Monteiro, João N.; Pinto, Miguel; Crespo, Daniel; Pardal, Miguel A.; Martinho, Filipe
Abstract: The increase in frequency and intensity of extreme climate events over the last few decades has been leading to profound changes in estuarine and marine ecosystems worldwide, with strong implications for the species inhabiting these ecosystems as well as for the services provided by them. In this study, we analysed the effects of climate variability on the temporal and spatial variations in population dynamics of the green crab Carcinus maenas in the Mondego estuary (Portugal), between 2003 and 2018. In this 15-year period, a greater recruitment of C. maenas was observed during drought periods, periods which was matched by an increase in secondary production. Ontogenic stage segregation was also observed, with juveniles being found mainly in the further upriver areas of the estuary. The estuarine population was mainly composed of the green morphotype, with the orange and red morphotypes present in more downstream areas of the estuary. Redundancy analysis (RDA) showed high spatial and temporal variability of C. maenas in the estuary which was related with environmental changes over the 15-year period. A correlation between C. maenas biological features and several local-scale (salinity and river runoff) and large-scale (North Atlantic Oscillation index and Eastern Atlantic pattern) environmental variables was identified through cumulative sums analysis (CUSUM), indicating a strong environmental control on C. maenas population dynamics. This paper shows the importance of relatively long-term datasets to unravel the effects of extreme weather events due to climate change on key epibenthic estuarine species, and also how they might cope with a changing marine environment. Highlights: Population dynamics and life cycle of Carcinus maenas are climate regulated. Local environmental factors were the main drivers for population distribution. Large-scale climate patterns affect the life cycle of the green crab. Dry years were revealed to be beneficial for Carcinus maenas.